(untitled) (Research, Society and Development, 2021)
Due to the increase in demand for dairy products, the study of their chemical compositions and the changes that occur during storage is extremely important. Therefore, it is necessary to develop efficient analytical techniques in the investigation of the constituent elements of such products, and X-ray energy dispersive spectroscopy (EDS) coupled to the scanning electron microscope (SEM) is a technique that is becoming explored in this context. Due to the lack of published works involving the aforementioned technique in the characterization of dairy products, this work aimed to expand the knowledge about the method in the dairy area. When analyzing dairy samples, SEM provides valuable information about particle morphology, which is critical in choosing target particles. Subsequently, through EDS, the elemental analysis of the surface of the target particles is performed. In the scientific literature, the use of EDS coupled with SEM to characterize samples of powdered milk is observed, with the predominance of the elements carbon and oxygen being reported, in addition to the presence of minerals. Still, the concentrations of carbon, oxygen and nitrogen, obtained through EDS, could be applied in a matrix formula that allowed the calculation of the surface content of constituent compounds of the samples, that is, proteins, lactose and fat. Therefore, from what was exposed in the course of the work, it can be concluded that EDS coupled to SEM is a microanalysis technique with great potential to be further explored and used in the elementary characterization of the surface of particles that make up dairy samples.